2022
DOI: 10.1177/10497323221119369
|View full text |Cite
|
Sign up to set email alerts
|

Doctors, Patients, and Interpreters’ Views on the Co-Construction of Empathic Communication in Interpreter-Mediated Consultations: A Qualitative Content Analysis of Video Stimulated Recall Interviews

Abstract: Doctors and patients rely on verbal and nonverbal resources to co-construct clinical empathy. In language-discordant consultations, interpreters’ communicative actions might compromise this process. We aim to explore doctors, patients, and professional interpreters’ perspectives on their own and others’ actions during their empathic interaction in interpreter-mediated consultations (IMCs). We analyzed 20 video stimulated recall interviews with doctors, patients, and interpreters using qualitative content analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Although the original German term has since fallen out of use, "empathy," as a concept, continues to be studied from different perspectives and in different contexts. It has been explored in clinical psychology and in clinical encounters (Riess et al, 2012), both for its importance in patient-provider interactions (see Riess et al, 2012;Boissy et al, 2016) and in interpreter-mediated scenarios (Krystallidou et al, 2018;Theys et al, 2023;Theys et al, 2022;Theys et al, 2021;Theys et al, 2020;Merlini & Gatti, 2015). There are various definitions of empathy in the literature, all of which suggest some form of feeling for another's pain and suffering (see Decety & Ickes, 2009).…”
Section: Defining Empathymentioning
confidence: 99%
“…Although the original German term has since fallen out of use, "empathy," as a concept, continues to be studied from different perspectives and in different contexts. It has been explored in clinical psychology and in clinical encounters (Riess et al, 2012), both for its importance in patient-provider interactions (see Riess et al, 2012;Boissy et al, 2016) and in interpreter-mediated scenarios (Krystallidou et al, 2018;Theys et al, 2023;Theys et al, 2022;Theys et al, 2021;Theys et al, 2020;Merlini & Gatti, 2015). There are various definitions of empathy in the literature, all of which suggest some form of feeling for another's pain and suffering (see Decety & Ickes, 2009).…”
Section: Defining Empathymentioning
confidence: 99%
“…In sum, these findings suggest that interpreters adapted their interpreting strategies to the doctor's lack of familiarity with their practices to avoid causing misunderstandings about the interpreter's level of professionalism during EC in IMCs. Future research should explore this hypothesis by analyzing the interpreters' accounts of the observed events (Theys et al, 2022).…”
Section: Interpreters Can Initiate Ec In Imcsmentioning
confidence: 99%
“…Interpreters might favor the doctor's expressions because doctors are often seen as the most powerful participant in the consultation (Hsieh, 2016). Future research should try to identify which factors influence interpreters' ways of rendering doctors' ERs and patients' EOs (Theys et al, 2022).…”
Section: Patient-initiated Ec In Imcs Might Be Compromisedmentioning
confidence: 99%
See 2 more Smart Citations